The Radio Sky at Meter Wavelengths: m-mode Analysis Imaging with the OVRO-LWA - Eastwood, Michael W.; Anderson, Marin M.; Monroe, Ryan M.; Hallinan, Gregg; Barsdell, Benjamin R.; Bourke, Stephen A.; Clark, M. A.; Ellingson, Steven W.; Dowell, Jayce; Garsden, Hugh; Greenhill, Lincoln J.; Hartman, Jacob M.; et al. (The Astronomical journal, 2018)
A host of new low-frequency radio telescopes seek to measure the 21 cm transition of neutral hydrogen from the early universe. These telescopes have the potential to directly probe star and galaxy formation at redshifts 20 z 7 but are limited by the dynamic range they can achieve against foreground sources of low-frequency radio emission. Consequently, there is a growing demand for modern, high-fidelity maps of the sky at frequencies below 200 MHz for use in foreground modeling and removal. We describe a new wide-field imaging technique for drift-scanning interferometers: Tikhonov-regularized m-mode analysis imaging. This technique constructs images of the entire sky in a single synthesis imaging step with exact treatment of wide-field effects. We describe how the CLEAN algorithm can be adapted to deconvolve maps generated by m-mode analysis imaging. We demonstrate Tikhonov-regularized m-mode analysis imaging using the Owens Valley Radio Observatory Long Wavelength Array (OVRO-LWA) by generating eight new maps of the sky north of δ = −30° with 15′ angular resolution at frequencies evenly spaced between 36.528 and 73.152 MHz and ∼800 mJy beam−1 thermal noise. These maps are a 10-fold improvement in angular resolution over existing full-sky maps at comparable frequencies, which have angular resolutions ≥2°. Each map is constructed exclusively from interferometric observations and does not represent the globally averaged sky brightness. Future improvements will incorporate total power radiometry, improved thermal noise, and improved angular resolution due to the planned expansion of the OVRO-LWA to 2.6 km baselines. These maps serve as a first step on the path to the use of more sophisticated foreground filters in 21 cm cosmology incorporating the measured angular and frequency structure of all foreground contaminants.